PENGARUH PELATIHAN, KOMPENSASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Pada PDAM Tirta Moedal Semarang) - Zimamul Fafa Fauzie, 13.05.51.0065; Yunianto, Askar (Students Journal of Economic and Management, 2018)
This study aims to analyze the influence of training, compensation, and work discipline on employee performance of PDAM Tirta Moedal Semarang. Types of data used are primary data is data obtained directly from the original source in the form of a questionnaire. Population in this research is employees of PDAM Tirta Moedal Semarang. Sampling was done by proportional random sampling technique with a total sample of 102 respondents. The Data collected were analyzed using factor analysis to test the validity of the question items, the reliability testing using cronbach alpha and hypothesis testing using multiple linear regression. The test results obtained that there is a positive and significant influence of training on employee performance, there is a positive and significant influence of compensation on employee performance, there is a positive and significant influence of labor discipline on employee performance.Keywords: Training, Compensation, Work Discipline and Employee Performance